Cover: JURNAL KEPERAWATAN MEDIA NERS VOLUME 2, NOMOR 1, 2007 - Pamungkas, Pradipta Ary (Department of Nursing, Faculty of Medicine, Diponegoro University, 2008)
JURNAL KEPERAWATAN MEDIA NERS VOLUME 2, NOMOR 1, 2007 Cover